Pengaruh Green Price dan Environmental Concern terhadap Green Product Purchase Intention - Desvia Syahra 10090322008; Dede R. Oktini; Mochamad Malik Akbar Rohandi (Bandung Conference Series: Business and Management, 2026)
Abstract. This research is motivated by the increasing problem of plastic waste, which has an impact on environmental damage. One effort to manage plastic waste is carried out by an environmental activist, Mr. Toni, who processes plastic waste into plastic-based paving block products. However, the success of plastic paving block products in the market is greatly influenced by consumer purchasing interest. Therefore, this study aims to determine the influence of green price and environmental concern on green product purchase intention for Mr. Toni's innovative plastic paving block products in the Padalarang area. This study employed quantitative methods with a descriptive and causality verification approach. Data were collected through questionnaires distributed to respondents who met the criteria for potential plastic paving block consumers in Padalarang District. The Slovin formula, with a 10% margin of error, was used as much 100 respondents, selected using purposive sampling. The research results show that green price and environmental concern influence green product purchase intention, both partially and simultaneously. Abstrak. Penelitian ini dilatarbelakangi oleh meningkatnya permasalahan sampah plastik yang terus meningkat. Salah satu upaya pengelolaan sampah plastik dilakukan oleh seorang pegiat lingkungan, yaitu Pak Toni, yang mengolah sampah plastik menjadi produk paving block berbahan dasar plastik. Namun, keberhasilan produk paving block plastik di pasar sangat dipengaruhi oleh minat beli konsumen. Oleh karena itu, penelitian ini bertujuan untuk mencari pengaruh green price dan environmental concern terhadap green product purchase intention pada produk paving block berbahan plastik inovasi Pak Toni di Wilayah Padalarang. Penelitian ini menggunakan metode kuantitatif dengan pendekatan deskriptif dan verifikatif kausalitas. Data dikumpulkan melalui penyebaran kuesioner kepada responden yang memenuhi kriteria sebagai calon konsumen produk paving block plastik di Kecamatan Padalarang. Untuk pencarian sampel menggunakan rumus Slovin dengan tingkat kesalahan sebesar 10%, sehingga jumlah sampel dalam penelitian ini sebanyak 100 responden yang terpilih menggunakan teknik purposive sampling. Hasil penelitian menunjukkan bahwa green price dan environmental concern memiliki pengaruh terhadap green product purchase intention, baik secara parsial maupun simultan.